Effects of User's Hand Orientation and Spatial Movements on Free Hand Interactions with Large Displays. Issue 6 (3rd June 2018) - Lou, Xiaolong; Peng, Ren; Hansen, Preben; Li, Xiangdong A.
ABSTRACT: In motion-sensing interaction with large displays through bare hands, we can observe that users alternate their hands and move their bodies frequently. What cause such actions and how these actions affect free hand interaction results are less systematically investigated. To address this gap in knowledge, we conducted studies on Pointer-Acceleration (PA)-based free hand interactions of target selection and found that (1) users made more frequent hand alternations when selecting small targets with large movement amplitudes, as in such cases users were not only affected by observable arm fatigue, but were also motivated to switch hands for higher selection accuracy and convenience; (2) hand alternation led to the hand orientation effects: target selection on display areas at the operating hand's side was more efficient and accurate than that at the opposite side; (3) large movement amplitudes on the user interface increased users' physical movements in front of the large display, which harmed selection efficiency; (4) selection of small targets led to a closer interaction distance, while large movement amplitudes led to a larger interaction distance; and (5) selection results were affected by interaction distances, as users gained high efficiency, but low accuracy at a large distance and low efficiency, but high accuracy at a close distance. Given these results, this article discusses practical implications for applying PA-based free hand interaction techniques and designing related user interfaces on large displays.